Youth transitions among descendants of turkish immigrants in Amsterdam and Strasbourg: a generation in transition (2019)
Writing this, I am sitting at a table in the library of a tertiary vocational school in Zwolle, a medium size Dutch city. I am surrounded by the descendants of immigrants from Turkey. They have no idea I am writing about them, much less that I understand, and admire, how they are talking in a creative half-Turkish half-Dutch argot. I catch their discussions, which are about everything ranging from the exams next week to the annoying boss at a bijbaan1 ; from worries about finding an apprenticeship to Turkish TV heartthrob Kıvanç Tatlıtuğ’s acting in last night’s episode; from the latest iPhone features to plans for next summer’s holiday in Istanbul; plus a whole lot of gossip about friends in between. Listening in on these conversions, I cannot help but wonder why doubts about these young people’s integration dominate current public debates rather than questions about their daily realities: the obstacles that they encounter at school and on the labour market; how they navigate these barriers and how they negotiate the multiple frames of references that enrich their lives. This book seeks to answer these questions, which have indisputable present-day urgency though actually began being asked decades ago.